Pojęcie zabudowy zagrodowej na tle przepisów o zagospodarowaniu przestrzennym - Świderski, Krzysztof (Wydawnictwo Naukowe UAM, 2013)
The aim of this paper is an analysis of the concept ‘farm building’ in light of article 41 clause 4 of the Act on Planning and Spatial Development and clarification of certain specific issues. Different interpretations of the same concept are presented, followed by rather impossible to accept consequences of such interpretations grounded in the regulations of construction law and agricultural law. Further, relationships between certain legal categories referred to in the Act, such as an agricultural holding, a dwelling plot, or a barnyard are discussed with an attempt to decide whether a dwelling house alone, if connected with an agricultural holding, may be treated in the same way as a farm building. The importance of the size factor in determining different categories of building permits and conditions has been also noted. Finally, the manner of determining land development conditions for small objects erected in small agricultural holdings is presented.

Lo scopo del lavoro è l’analisi del concetto di “fattoria” alla luce dell’art. 61, comma 4 della legge sulla pianificazione ed edificazione territoriale e la risoluzione di una serie di problemi specifici. L’autore presenta diverse interpretazioni di questo concetto e le conseguenze, difficili da accettare, dell’interpretazione riferentesi alla comprensione del concetto discusso sullo sfondo delle norme del diritto edilizio e agrario. Egli descrive anche il rapporto tra la fattoria e le categorie giuridiche quali azienda agricola, appezzamento di terreno destinato all’insediamento e cortile nonché risponde alla domanda se l’edificio abitativo stesso, collegato all’azienda agricola, può essere equiparato alla fattoria. L’attenzione è stata posta anche sull’importanza del criterio territoriale in materia di determinare le condizioni edificatorie per la fattoria. Alla fine è stata presentata la procedura da seguire nel determinare le condizioni edificatorie per gli edifici collocati nelle piccole aziende agricole.
A concept of a ‘farm building’ in light of the provisions regulating spatial development
Il concetto di fattoria sullo sfondo delle norme sull’edificazione territoriale